2021
DOI: 10.1177/02601060211009033
|View full text |Cite
|
Sign up to set email alerts
|

How will the way we live look different in the wake of the COVID-19 pandemic? A nutrition survey in Greece

Abstract: Background: As we move towards a post-pandemic society, a question arises: How will the way we live look different in the wake of the COVID-19 pandemic? Aim: The aim of this survey was to evaluate changes in eating habits and other lifestyle behaviours (i.e., exercise and smoking) of people of almost all ages, who live in Greece, during the COVID-19 pandemic. Methods: A web-based survey using conventional sampling was conducted from during December 2020, in Greece. A total of 2258 individuals, aged 17 years an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Thus, before the pandemic, similar studies revealed high percentages of history of DS use (e.g., Switzerland 53% [ 26 ] and Saudi Arabia 63.2% [ 16 ]); meanwhile, others examined DS usage using a relatively wide usage timeframe, such as during the last one or two years (e.g., Spain: 9.3% [ 7 ], Poland: 10% [ 8 ], France: 40.8% [ 27 ], Italy: 49% [ 22 ], Netherlands: 62% [ 18 ] and Lithuania: 66.1% [ 9 ]) or a narrower range, such as during the previous week/month (e.g., France: 24.8% [ 27 ], Greece: 31.4% [ 12 ], Australia: 43.2% [ 28 ], Denmark: 55.8% [ 21 ] and USA: 57.6% [ 29 ]). Indeed, many studies have shown an increase in DS use after the pandemic began (e.g., Spain: 21.3% [ 10 ], Poland: 48–79% [ 11 ] and Lithuania: 78.1% [ 9 ]), with Greece, however, showing mixed results [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, before the pandemic, similar studies revealed high percentages of history of DS use (e.g., Switzerland 53% [ 26 ] and Saudi Arabia 63.2% [ 16 ]); meanwhile, others examined DS usage using a relatively wide usage timeframe, such as during the last one or two years (e.g., Spain: 9.3% [ 7 ], Poland: 10% [ 8 ], France: 40.8% [ 27 ], Italy: 49% [ 22 ], Netherlands: 62% [ 18 ] and Lithuania: 66.1% [ 9 ]) or a narrower range, such as during the previous week/month (e.g., France: 24.8% [ 27 ], Greece: 31.4% [ 12 ], Australia: 43.2% [ 28 ], Denmark: 55.8% [ 21 ] and USA: 57.6% [ 29 ]). Indeed, many studies have shown an increase in DS use after the pandemic began (e.g., Spain: 21.3% [ 10 ], Poland: 48–79% [ 11 ] and Lithuania: 78.1% [ 9 ]), with Greece, however, showing mixed results [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such a shift among Greek consumers was recently shown to be insignificant, with roughly one in three having used a DS in the previous two weeks [ 12 ]; yet, a recent Greek study showed that ~35% and ~20% of its participants had shifted towards healthier nutrition and started/increased their DS consumption in order to enhance their immune system, respectively [ 13 ]. However, besides these two recent Greek studies, to our knowledge only two other studies have examined the usage of DS in Greece; namely, the European Prospective Investigation into Cancer and Nutrition (EPIC) study, which found a usage rate of 2% for men and 6.7% in women (24 h prior) between 1995 and 2000 [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the population-based survey studies, thirty-one were conducted through online surveys only ( 17 , 18 , 20 , 22 , 23 , 25 , 26 , 28 31 , 35 , 42 , 43 , 45 , 48 54 , 57 62 , 66 , 68 , 74 ), one was an in-person interview ( 56 ), three were telephone interviews ( 10 , 21 , 38 ), and two were both in-person and online surveys ( 19 , 36 ). Among the included studies, usage status of the interventions, including TCM ( n = 22) ( 27 , 32 34 , 37 , 39 , 40 , 44 , 47 , 55 , 63 65 , 67 , 69 73 , 75 77 ), functional food (supplements) or herbs ( n = 20) ( 17 24 , 29 , 36 , 38 , 43 , 49 52 , 57 59 ), mind-body practice or spiritual practice ( n = 9) ( 28 , 35 , 42 , 45 , 48 , 54 , 60 , 61 , 74 ), Ayurveda ( n = 2) ( 10 , 41 ), homeopathy ( n = 1) ( ...…”
Section: Resultsmentioning
confidence: 99%
“…Most of the data for surveys or patient chart reviews were collected during 2020. In approximately half of the studies, TCIM interventions were used for prophylactic purposes ( n = 28) ( 17 20 , 22 , 23 , 25 , 26 , 28 , 31 , 35 , 36 , 38 , 41 , 42 , 45 , 48 54 , 59 , 61 , 62 , 66 , 74 ), and the other half were used for therapeutic purposes ( n = 27) ( 21 , 24 , 27 , 32 34 , 37 , 39 , 40 , 44 , 46 , 47 , 55 , 58 , 63 65 , 67 , 69 73 , 75 77 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nearly one in three of 2258 participants reported that they changed their dietary habits during the pandemic towards a healthier diet rich in fruits, vegetables, salads, green vegetables, cereals, legumes, and olive oil, and consumed less meat, especially processed meat [ 110 ]. Similarly, another study of 741 individuals report a prudent dietary pattern containing of fruits, vegetables, fish, and rice [ 111 ].…”
Section: Covid-19 and Comorbiditiesmentioning
confidence: 99%